Pengaruh Project Based Learning terhadap Kreativitas dan Hasil Belajar Pada Mata Pelajaran Animasi 2D dan 3D di SMK Unitomo - Syahmi, Favian Avila; Mustaji, Mustaji; Maureen, Irena Yolanita (LP. Ma'arif Janggan Magetan, 2024)
This study aims to determine the influence of the Project Based Learning learning model on the creativity and learning outcomes of grade XI students at SMK UNITOMO Surabaya, focusing on 2D and 3D Animation subjects and Basic Principles of Making 2D Animation. This research method uses quantitative research methods with a Quasi Experiment design. The sample of this study consisted of 22 grade A students as an experimental class and 22 class B as a control class at SMK UNITOMO, using performance tests and questionnaires as research instruments. The test results showed that the value of the t test results on the posttest value of student creativity was known to be the mean value of the control group 72.31 and the mean value of the experimental group was higher with a score of 84.90. And the results of the t test on the posttest value of student learning outcomes are known to be the mean value of the control group 80.59 and the mean value of the experimental group is higher with a score of 83.77. Thus, it can be concluded that there is a positive influence of the use of the Project Based Learning model on the creativity and learning outcomes of grade XI students at SMK UNITOMO Surabaya in 2D and 3D animation subjects material Basic Principles of Animation Making.